Censorship: WhatsApp (Pakistan) - Voidly (2024)
CRITICAL severity censorship detected in Pakistan. Confidence: 75%. Data sourced from CensoredPlanet.
Censorship Incident ID: PK-2024-0003
Keywords: censorship; PK; censorship; critical